KARAKTERISTIK MUTU KITOSAN DARI KULIT TERIPANG PASIR (Holothuria scabra) DENGAN WAKTU PEMANASAN BERBEDA - ulil_amri ulil_amri; mirna_ilza mirna_ilza; sumarto_sumarto sumarto_sumarto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study aims to determine the quality characteristics and degrees of chitosan deacetylation of sea cucumber Holothuria scabra skin extracted in different heating time. The reserach was conducted by using experimental method, that was extracting the skin of sea cucumber Holothuria scabra by heating it in extractor NaOH solution for varied time (90, 120 and 150 minutes) to produce chitosan flour. The results showed that the sea cucumber skin was containing of 5,26% water, 17,96% protein, 0,40% fat, 61,11% ash and 17,13% carbohydrate. The yield of chitin flour was 40,40%. It was containing of moisture 5,27%, ash 6,02%, with deacetylation degree of 38,84%. The different of heating time was siginificantly affecting to the quality of the chitosan flour produced. Extracting the skin of sea cucumber by heating it for 150 minutes produced the best quality of chitosan, indicated by the yield of 33,11%, moisture content of 5,96%, ash content of 6,65%, with deacetylation degree of 69,65%.